Analysis of the factors that influence the performance of MSME employees in Gianyar Regency - I Gede Putu Kawiana (Lead Journal of Economy and Administration, 2023)
The objective of this study is to identify the variables that influence the performance of employees within the Silver Crafts UMKM Association located in Celuk Village, Sukawati District, Gianyar Regency, Bali. The variables employed in this research encompass remuneration, job motivation, and work discipline. The present study employs primary data. The study's population and sample consisted of 45 employees who were affiliated with the UMKM association of silver traders in Celuk Village, Sukawati District, Gianyar Regency, Bali. The sample technique employed in this study utilizes a saturated sampling approach. The present study employs many statistical tests, including validity and reliability assessments, as well as partial and multiple determination coefficient tests. Additionally, the study utilizes partial and simultaneous hypothesis testing through the utilization of the SPSS type 26 application. The findings indicate that (1) partial compensation has a statistically significant impact on Employee Performance, (2) partial work motivation has a statistically significant impact on Employee Performance, (3) partial work discipline does not have a statistically significant impact on Employee Performance, and (4) when considered together, compensation, work motivation, and work discipline have a statistically significant impact on employee performance.